(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
Understanding compound sentences with adverse clauses is essential for mastering the intricacies of both English and Uzbek grammar. These sentences allow speakers to express contrasting ideas within a single sentence, enhancing the richness and clarity of communication. This article will explore the structure, use, and nuances of compound sentences with adverse clauses in both English and Uzbek, highlighting similarities and differences between the two languages.